Inhaled sedation versus propofol in respiratory failure in the ICU (INSPiRE-ICU2): study protocol for a multicenter randomized controlled trial - Brian O’Gara; Alexis L. Serra; Joshua A. Englert; Alisha Sachdev; Robert L. Owens; Steven Y. Chang; Pauline K. Park; Daniel Talmor; Ida Sverud; Peter Sackey; Jeremy R. Beitler (Trials)
Abstract Background Patients undergoing invasive mechanical ventilation often require pharmacologic sedation to facilitate tolerance of this life-sustaining intervention, but sedatives currently used in routine care have substantial limitations. Isoflurane is an inhaled volatile anesthetic with pharmacologic properties potentially suitable to sedation of ventilator-dependent critically ill patients, but need for specialized drug administration equipment has limited its use historically to general anesthesia in the operating theatre. This trial will evaluate isoflurane, administered using a novel drug delivery system, for sedation of ventilator-dependent adult intensive care unit (ICU) patients in the United States (US). Methods The Inhaled Sedation versus Propofol in Respiratory Failure in the ICU (INSPiRE-ICU2) is a phase 3, multicenter, randomized, controlled, assessor-blinded non-inferiority trial that will evaluate efficacy and safety of inhaled isoflurane delivered via the Sedaconda ACD-S, compared to intravenous propofol, for sedation of mechanically ventilated adult ICU patients. At 16 US hospitals, 235 enrolled patients requiring continuous sedation during invasive mechanical ventilation will be randomized in 1.5:1 ratio to inhaled isoflurane or intravenous propofol for sedation. Treatment duration is expected to be at least 12 h and may last up to 48 (± 6) h or until no longer needing continuous sedation, whichever occurs first. The primary endpoint is the percentage of time sedation depth is maintained within the targeted range (Richmond Agitation Sedation Scale − 1 to − 4), in the absence of rescue sedation, during the treatment period. Secondary superiority outcomes include opioid exposure, wake-up time, cognitive recovery after end-of-treatment, and preservation of spontaneous breathing effort. Discussion The INSPiRE-ICU2 trial will help determine the potential role of isoflurane for sedation of ventilator-dependent adult patients in the ICU. Key trial design features, including adoption of the estimand framework and blinded assessments of sedation depth, pain, and cognitive recovery, will ensure a rigorous evaluation of isoflurane for ICU sedation. Trial registration ClinicalTrials.gov, NCT05327296. First registered on April 5, 2022.